Effective Daylighting: Evaluating Daylighting Performance in the San Francisco Federal Building from the Perspective of Building Occupants - Kyle S. Konis (Architecture, 2012)
Commercial office buildings promoted as “sustainable,” “energy efficient,” “green,” or “high performance” often reference use of daylight as a key strategy for reducing energy consumption and enhancing indoor environmental quality. However, buildings are rarely studied in use to examine if the design intent of a sufficiently daylit and a visually comfortable work environment is achieved from the perspective of building occupants or how occupant use of shading devices may affect electrical lighting energy reduction from photocontrols. This dissertation develops a field-based approach to daylighting performance assessment that pairs repeated measures of occupant subjective response using a novel desktop polling station device with measurements of the physical environment acquired using High Dynamic Range (HDR) imaging and other environmental sensors with the objective of understanding the physical environmental conditions acceptable to occupants. The approach is demonstrated with a 6-month field study involving (N=44) occupants located in perimeter and core open-plan office spaces in the San Francisco Federal Building1 (SFFB). Over 23,100 subjective assessments paired with physical measures were analyzed to develop models of visual discomfort and shade control and to examine the assumptions of existing daylighting performance indicators. The analysis found that existing daylight performance indicators overestimated the levels of daylight illuminance required by occupants to work comfortably without overhead ambient electrical lighting. Time-lapse observation of interior roller shades showed that existing shade control models overestimated the frequency of shade operation and underestimated the level of facade occlusion due to interior shades. Comparison of measured results to the daylighting objectives of the SFFB showed that available daylight enabled electrical lighting energy reduction in the perimeter zones but not in the open-plan core zones. The results extend existing knowledge regarding the amount of daylight illuminance acceptable for occupants to work comfortably without overhead electrical lighting and for the physical variables (and stimulus intensities) associated with visual discomfort and the operation of interior shading devices.
Keywords: daylighting; performance assessment; San Francisco Federal Building; shading controls